2001
DOI: 10.1016/s1074-7613(01)00249-7
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila Scavenger Receptor CI Is a Pattern Recognition Receptor for Bacteria

Abstract: One hallmark of innate immunity apparently conserved from primitive life forms through to humans is the ability of the host to recognize pathogen-associated molecular patterns (PAMPs). Since macrophage pattern recognition receptors are not well defined in Drosophila, we set out to identify such receptors. Our findings reveal that Drosophila macrophages express multiple pattern recognition receptors and that the Drosophila scavenger receptor, dSR-CI, is one such receptor capable of recognizing both gram-negativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
167
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 236 publications
(179 citation statements)
references
References 55 publications
9
167
0
1
Order By: Relevance
“…This discrepancy in results may reflect inherent differences in the assays. The S2 cell phagocytosis assay is able to detect quantitative differences in phagocytosis using fluorescence-activated sorting, but does not directly distinguish between bacteria at the surface and internalized bacteria (21). The in vivo assay by our method is not as quantitative but is able to test mutations in the animal where the phagocytes are in their natural cellular environment and detects only internalized bacteria.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This discrepancy in results may reflect inherent differences in the assays. The S2 cell phagocytosis assay is able to detect quantitative differences in phagocytosis using fluorescence-activated sorting, but does not directly distinguish between bacteria at the surface and internalized bacteria (21). The in vivo assay by our method is not as quantitative but is able to test mutations in the animal where the phagocytes are in their natural cellular environment and detects only internalized bacteria.…”
Section: Discussionmentioning
confidence: 96%
“…PGRP-LC, -LE, and -SA have been demonstrated to bind peptidoglycan and are necessary for expression of AMP genes (6,10,17,19,20), supporting the hypothesis that PGRPs directly recognize bacteria and activate immune responses. The identification of mutations in PGRP-SA (seml) and PGRP-LC (ird7 or totem) indicated that these genes are necessary for activation of the two signaling pathways regulating AMP gene expression, the Toll pathway that responds to Gram ϩ bacteria and fungi and the Imd pathway that responds to Gram Ϫ bacteria (4,5,8,21). Drosophila uses PGRP-SA and PGRP-LC to distinguish between Gram ϩ and Gram Ϫ PGN for activation of the Toll and Imd signaling pathways (7).…”
mentioning
confidence: 99%
“…In order for phagocytosis to occur, receptors on the surface of the engulfing cell must first recognize an invading pathogen or apoptotic body. Previous studies in insects have identified a number of conserved proteins, including complement-like factors, pathogen-recognition receptors, and cytoskeletal proteins necessary for proper phagocytosis (52)(53)(54)(55)(56). In mammals and insects, activation of surface receptors induces intracellular signaling pathways leading to the cytoplasmic remodeling required for internalization, phagosome maturation, and particle dissolution.…”
Section: Phagocytosismentioning
confidence: 99%
“…One of the first to be identified was the scavenger receptor dSR-CI as a pattern recognition receptor that binds to bacteria (56). This receptor is responsible for only a small amount of the total binding of bacteria by a phagocytically active Drosophila cell line.…”
Section: Phagocytosismentioning
confidence: 99%
“…Building on the identification of Serpent as an important factor required for efficient phagocytosis in S2 cells, Kocks et al performed expression profiling and identified 45 genes that were down-regulated by depletion of Serpent [27] (Table 1). Among those genes was SR-C1, a phagocytic scavenger receptor [28]. RNAi against these Serpent-dependent genes also identified a novel phagocytic receptor, Eater.…”
Section: Microbial Recognition and Survival Screensmentioning
confidence: 99%